Legumes of Africa - a check list - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Legumes of Africa: a check-list, J.M. Lock, 1989, 619pp paperback, ISBN 0 94764310 9, price UKL15.00,